DENTAL SERVICES MARKETING IN PRACTICES - Daryono; Wirawan Dony Dahana; Yuary Farradia (RADJA PUBLIKA, 2025)
Introduction: The rapid development and change in the digital world has had a big impact on the world of dentistry. Digital marketing is very good in the process of doing marketing management that can be applied to the intention of visiting dental care to dental clinics. Objective: To find out the digital marketing strategy in daily dental services. Method: The method of searching for articles on digital marketing strategies for dental services in dental clinics in electronic databases is Semantic Scholar. The total initial search results in the database totaled 1000 articles using the keyword